"You can come whenever you like - all you gotta do is ask" [Defence Minister Robert Ray talking to Japan's Emperor Hakihito] - Pryor, Geoff, 1944- (1992)
While on a state visit to Japan Prime Minister Paul Keating issues an invation to Emperor Hakihito to visit Australia. Defence Minister Robert Ray provides further reassurance.--Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 1 October 1992.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Ray, Robert, -- 1947- -- Caricatures and cartoons; Politicians -- Australia -- Caricatures and cartoons; Australia -- Foreign relations -- Indonesia -- Caricatures and cartoons; Australia -- Foreign relations -- 1990-2001 -- Caricatures and cartoons; Australia -- Politics and government -- 1990-2001 -- Caricatures and cartoons